The identification of parameters for visco-plastic models via finite-element methods and gradient methods - Mahnken, Rolf; Stein, E (Modelling and Simulation in Materials Science and Engineering)
Keywords: Computer Science Applications; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Efficient integration technique for generalized viscoplasticity coupled to damage - Johansson, Magnus; Mahnken, Rolf; Runesson, Kenneth (International Journal for Numerical Methods in Engineering)
Keywords: Applied Mathematics; General Engineering; Numerical Analysis

Parameter identification for viscoplastic models based on analytical derivatives of a least-squares functional and stability investigations - Mahnken, Rolf; Stein, Erwin (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Parameter identification for finite deformation elasto-plasticity in principal directions - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Aspects on the finite-element implementation of the Gurson model including parameter identification - Mahnken, Rolf (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Zum Lehren mit neuen Medien im Physikunterricht - Jonas-Ahrend, Gabriela; Reinhold, Peter

Construction of Pseudorandom Functions - Fricke, Birgitta
Keywords: Diplomarbeit

Bazin - Bartz, Christina (Metzler-Lexikon Medientheorie Medienwissenschaft. Ansätze – Personen – Grundbegriffe)

Spiegel und Zauberspiegel. Die Beobachtung und Konstruktion des Fernsehens in der frühen Bundesrepublik - Bartz, Christina (Medienkultur der 50er Jahre)

Die Masse allein zu Hause. Alte Funktionen und neue Medien - Bartz, Christina (Medienkultur der 50er Jahre)

MedienUmstellung. Vom Hör- zum Fernsehspiel - Bartz, Christina (Medienkultur der 50er Jahre)

Evaluierung und Implementierung eines vollständig verteilten RSA-Kryptographiesystems - Deveci, Deniz
Keywords: Diplomarbeit

The Weil-Pairing and Signature Schemes in Elliptic Curve Cryptography - Helbich, Anke
Keywords: Diplomarbeit

Timing Attacks for Cryptosystems based on Elliptic Curves - Schepers, Daniel
Keywords: Diplomarbeit

Beobachtungsobjekt Massenmedium. Der Fernsehzuschauer zwischen Konzentration und Zerstreuung - Bartz, Christina (Fakten und Fiktionen. Über den Umgang mit Medienwirklichkeiten)

Telepathologien. Der Fernsehzuschauer unter medizinischer Beobachtung - Bartz, Christina (Medienkultur der 50er Jahre)

Implementierung und Evaluation eines MDS-Blockcodes mit unabhängigen Paritätssymbolen - Hoppe, Ulrich

Quiz - Bartz, Christina (Metzler-Lexikon Medientheorie Medienwissenschaft. Ansätze – Personen – Grundbegriffe)

Repetitive Innovation? Die Frankfurter Sound-Art-Ausstellung "Frequenzen [Hz] Audiovisuelle Räume" - Jacke, Christoph (Telepolis)

Phänomenologie der Phänomenologie. Systematik und Methodologie der Phänomenologie in der Auseinandersetzung zwischen Husserl und Fink. - Luft, Sebastian
A shortened and heavily revised version of my dissertation from 1998.